Distress, coping and emotional health during the gradual opening of university systems, post COVID19, in India - Shilpa Ashok Pandit; Amit A. Nanavati; Bijal Mehta; Sonal Yadav (International Journal of Adolescence and Youth)
The present research reports the emotional health of students in the context of the gradual opening up of the university systems in India, when students (re)joined the university in person. 430 students participated in an online trust reference-based survey. The items included in the survey questionnaire were based on initial four focused group discussions with students. Survey results show that overall students’ adjustment was significantly influenced by their personal strengths and ability to manage academic challenges after controlling for other factors. Discriminant Function Analysis (DFA) and Binary Logistic Regression Analysis revealed that the key differentiator between the distressed group and others was whether the student reported their ability to share feelings with family members. Feeling excluded and having no one to talk to were the significant predictors for student distress.